Artrogripose renal colestática diagnosticada a partir de colestase neonatal: relato de caso - Bruna Caseri Marino; Natascha Silva Sandy; Gabriel Hessel; Maria Angela Bellomo Brandão (Sociedade Brasileira de Pediatria, 2022)
Arthrogryposis, renal dysfunction and cholestasis (ARC) syndrome is a rare autosomal recessive syndrome, with multisystemic manifestations and mainly characterized by arthrogriposis, renal dysfunction and cholestasis. The prognosis is poor and most patients die within the first year of life. This is a case report of a female infant, 37 days old, referred to a tertiary hospital due to neonatal cholestasis. Upon evaluation, she also presented with Fanconi syndrome, arthrogryposis, malnutrition, ichthyosis and agranular platelets, thus receiving the clinical diagnosis of ARC syndrome. The liver biopsy showed signs of neonatal hepatitis. Her admission was complicated by dehydration, worsening of metabolic acidosis and acute respiratory failure. The infant was discharged at the age of 3 months, in palliative care, and later died. As it is a very rare disease, knowledge of its characteristics is crucial for appropriated diagnostic evaluation and differential diagnosis with other causes of cholestasis, as well as adequate management.